2012
DOI: 10.4172/2161-0495.s1-007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Treatment of Severe Poisoning in the Intensive Care Unit: Lessons from a One-Year Prospective Observational Study

Abstract: Background: Acute poisoning is a frequent cause of admission to emergency departments (ED) and often requires treatment in the intensive care unit (ICU). The objective of this study is to characterize the patients admitted to an ICU in a toxicology referral center in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…This is comparable with the findings of previous studies; Singh et al (2011) found that 50.7% of the studied cases were males and from age group 21 to 30 years in a study done in a tertiary care hospital in the metropolitan city of New Delhi. Taghaddosinejad et al (2012) showed that the majority of the studied patients were young (below 30 years); males (57%) and either employed (40.2%), students or housewives.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This is comparable with the findings of previous studies; Singh et al (2011) found that 50.7% of the studied cases were males and from age group 21 to 30 years in a study done in a tertiary care hospital in the metropolitan city of New Delhi. Taghaddosinejad et al (2012) showed that the majority of the studied patients were young (below 30 years); males (57%) and either employed (40.2%), students or housewives.…”
Section: Discussionmentioning
confidence: 91%
“…However, in Iran (Baharloo Hospital, Tehran. ), life-threatening poisoned patients requiring ICU admission constituted 8% of the total poisoned cases admitted during one year (Taghaddosinejad et al, 2012). Arıkan et al (2014) found that acute intoxications constituted 7.61% of the admitted patients to ICU of Karabük Training and Research Hospital in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 10% of the 80 million total Iranian population are living in Tehran and these two main referral centres serve 10% of the population of the country 19 , 25 . We therefore estimate that 42 940 patients in the country were possibly treated for lead poisoning, of whom nearly 20 000 received lead-chelating agents (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Poisoning with fatal agents such as aluminum phosphide, paraquat, organophosphate, or massive pharmaceutical drug overdoses usually needs ICU care and sometimes mechanical ventilation [5,6]. A question is therefore arisen: which of these agents is better to be used for ulcer prophylaxis in poisoned patients?…”
Section: Letter To the Editormentioning
confidence: 99%